Transfer effects of practice for simple alternating movements - Koeneke, S.; Battista, C.; Jancke, L.; Peters, M. (Journal of Motor Behavior, 2009)
In studies on transfer of practice effects, researchers use simple or complex movements that involve a significant cognitive element. In the present study, the authors studied intermanual and intramanual transfer of practice with a task that can be considered intermediate in difficulty. Using finger tapping as a motor task, 30 participants practiced tapping 6 days per week for 2 weeks with the left or right middle finger in a between-subject design. Compared with controls, the unpracticed middle finger of both hands showed significant improvement, along with all of the other unpracticed digits. There was no significant difference in the strength of transfer from the practiced finger to other fingers of the same (intramanual transfer) or the other (intermanual transfer) hand. The authors did not observe an asymmetry of transfer effects (the degree to which transfer depends on the particular hand trained). Last, in terms of speed and regularity of movement, the digits broke down into 2 different clusters; the thumb, index finger, and middle finger formed 1 cluster superior to that formed by the ring and small fingers.